Analisis Miskonsepsi Peserta Didik di SMAN 7 Padang Pada Konsep Keanekaragaman Hayati - Dian Purnama Sari; Heffi Alberida (Universitas Sultan Ageng Tirtayasa, 2022)
This research is motivated by the problem of the low cognitive competence of students in learning Biology at SMAN 7 Padang which is closely related to misconceptions. The purpose of this study was to determine the percentage of students who experienced misconceptions on the subject of biodiversity. This research is a descriptive study, the data collection technique that the author uses is to use questions given to students, with this question the authors obtain data about students' misconceptions on biodiversity material at SMAN 7 Padang. Afterthe data was obtained, the writer used a descriptive statistical formula. Theresearch subjects were 40 students of class X, which was carried out from July to August 2021. After the research was carried out, the authors obtained the results of the research on the percentage of misconceptions experienced by students in the sub-material of the concept of biodiversity of 45.00%, the sub-material of biodiversity at the level of genes, species and species by 39.08%, sub-material types of aquatic ecosystems and terrestrial ecosystems by 38.33%, sub-material diversity and distribution of flora and fauna in Indonesia by 41.25%, sub-materialbenefits of biodiversity in Indonesia by 55.00%, sub-material factors causing the reduction of biodiversity in Indonesia by 32.50%, submaterial 37.50%.